Sex differences in risk factor management of coronary heart disease across three regions. Issue 20 (20th September 2017) - Zhao, Min; Vaartjes, Ilonca; Graham, Ian; Grobbee, Diederick; Spiering, Wilko; Klipstein-Grobusch, Kerstin; Woodward, Mark; Peters, Sanne AE
Abstract : Objective: To investigate whether there are sex differences in risk factor management of patients with established coronary heart disease (CHD), and to assess demographic variations of any potential sex differences. Methods: Patients with CHD were recruited from Europe, Asia, and the Middle East between 2012-2013. Adherence to guideline-recommended treatment and lifestyle targets was assessed and summarised as a Cardiovascular Health Index Score (CHIS). Age-adjusted regression models were used to estimate odds ratios for women versus men in risk factor management. Results: 10 112 patients (29% women) were included. Compared with men, women were less likely to achieve targets for total cholesterol (OR 0.50, 95% CI 0.43 to 0.59), low-density lipoprotein cholesterol (OR 0.57, 95% CI 0.51 to 0.64), and glucose (OR 0.78, 95% CI 0.70 to 0.87), or to be physically active (OR 0.74, 95% CI 0.68 to 0.81) or non-obese (OR 0.82, 95% CI 0.74 to 0.90). In contrast, women had better control of blood pressure (OR 1.31, 95% CI 1.20 to 1.44) and were more likely to be a non-smoker (OR 1.93, 95% CI 1.67 to 2.22) than men. Overall, women were less likely than men to achieve all treatment targets (OR 0.75, 95% CI 0.60 to 0.93) or obtain an adequate CHIS (OR 0.81, 95% CI 0.73 to 0.91), but no significant differences were found for all lifestyle targets (OR 0.93, 95% CI 0.84 to 1.02). Sex disparities in reaching treatment targets were smaller in Europe than in Asia and the Middle East. Women in Asia were more likely than men to reach lifestyle targets, with opposing results in Europe and the Middle East. Conclusions: Risk factor management for the secondary prevention of CHD was generally worse in women than in men. The magnitude and direction of the sex differences varied by region.